Work from Home: Menuju Kinerja Aparatur Sipil Negara Yang Lebih Efisien - Sagita Sagita Wirasistha; ayu widowati (Institut Pemerintahan Dalam Negeri (IPDN), 2023)
The implementation of Work from Home (WFH) in government administration has had significant impacts and phenomena. The government needs to consider several things in implementing WFH so that it can take appropriate steps to overcome negative impacts and maximize benefits. In this study, the objectives were to analyze the implementation of Work From Home, examine the obstacles in implementing Work from Home, and examine the impact of Work From Home on the performance of the State Civil Apparatus. field in the Human Resources Development Agency of West Java Province. And also using the literature study method, namely Work From Home. Based on the results of the study, the implementation of Work From Home at the West Java Province Human Resource Development Agency went well and no significant obstacles were found and the performance of employees was maintained while prioritizing service to the community and continuing to strictly implement health protocols